Species Diversity, Structure, and Regeneration Status of Woody Plants in Saleda Yohans Church Forest, South Wollo, Ethiopia - Amare Bitew Mekonnen; Ali Seid Mohammed; Aster Demissew (Scientifica)
The study was conducted to determine woody plant species composition, structure, and regeneration status in Saleda Yohans Church forest, South Wollo Zone, Ethiopia. Five transect lines oriented to north-south directions at a distance of about 500 m were laid down along transects across the forest. Fifty main plots of 20 m × 20 m were laid for tree/shrub data collection. Within each main plot, 5 small quadrats of 5 m × 5 m were laid in the corners and centre for the collection of seedling and sapling data of woody species. All vegetation data within the plots were counted and recorded. Tree height and diameters at the breast height of plants were also measured and estimated. Moreover, frequency, basal area, diversity, evenness, and other vegetation data were analyzed. The result showed that this Church forest is composed of 50 woody plant species distributed in 31 families. The Shannon–Wiener diversity index and evenness values of the forest were found to be 3.82 and 0.84, respectively. Lamiaceae was the dominant family followed by Fabaceae in their species composition. The density of trees/shrubs, saplings, and seedlings was 625, 650, and 935 ha−1, respectively. Based on the result, the entire vegetation of Saleda Yohans Church forest is in good regeneration status. In conclusion, although this Church forest appears to be in a good regeneration status, its species richness is low compared to a similar study of some other vegetation. Therefore, attention should be given to the rehabilitation of this forest.